Dynamics of Pd Dopant Atoms inside Au Nanoclusters during Catalytic CO Oxidation - Garcia, Clara (J Phys Chem C Nanomater Interfaces, 2020)
[Image: see text] Doping gold nanoclusters with palladium has been reported to increase their catalytic activity and stability. PdAu(24) nanoclusters, with the Pd dopant atom located at the center of the Au cluster core, were supported on titania and applied in catalytic CO oxidation, showing significantly higher activity than supported monometallic Au(25) nanoclusters. After pretreatment, operando DRIFTS spectroscopy detected CO adsorbed on Pd during CO oxidation, indicating migration of the Pd dopant atom from the Au cluster core to the cluster surface. Increasing the number of Pd dopant atoms in the Au structure led to incorporation of Pd mostly in the S–(M–S)(n) protecting staples, as evidenced by in situ XAFS. A combination of oxidative and reductive thermal pretreatment resulted in the formation of isolated Pd surface sites within the Au surface. The combined analysis of in situ XAFS, operando DRIFTS, and ex situ XPS thus revealed the structural evolution of bimetallic PdAu nanoclusters, yielding a Pd single-site catalyst of 2.7 nm average particle size with improved CO oxidation activity.